Advantage of magnifying narrow‐band imaging for the diagnosis of colorectal neoplasia associated with sessile serrated lesions - Yuri Enomoto; Mitsuaki Ishioka; Akiko Chino; Hikari Kobayashi; Ryo Shimizu; Chihiro Yasue; Daisuke Ide; Masahiro Igarashi; Junko Fujisaki; Takahisa Matsuda; Yoshinori Igarashi; Shoichi Saito (DEN Open)
Abstract Objectives This study aimed to extract endoscopic findings for diagnosing colorectal neoplasia associated with sessile serrated lesions (SSLs), which are of significant interest. Methods To compare the magnifying narrow‐band imaging (NBI) findings with microscopic morphology, we classified SSLs into two groups: Group A SSLs included the majority of uniform SSLs and any dysplasia other than that classified as group B SSLs. Group B SSLs included SSLs with intramucosal and invasive carcinoma. We also quantitatively assessed visible vessels using ImageJ software. Results This study included 47 patients with 50 group B SSLs who underwent endoscopic resection between 2012 and 2020. The results were retrospectively compared with those of 237 patients with 311 group A SSLs that underwent endoscopic resection. Using conventional white‐light endoscopy, significantly more group B SSLs had uneven shapes and some reddening compared to group A SSLs. The diagnostic odds ratios for group B SSLs were as follows: lesions with a diameter ≥10 mm, 9.76; uneven shape, 3.79; reddening, 15.46; and visible vessels with NBI, 11.32. Regarding visible vessels with NBI, the specificity and diagnostic accuracy for group B SSLs were 94.9% and 93.1%, respectively. The percentage of the vascular tonal area of NBI images was significantly larger for group B SSLs than for group A SSLs (3.97% vs. 0.29%; p < 0.01). Conclusions SSLs with reddening and/or a diameter ≥10 mm are suspected to contain cancerous components. Moreover, visible vessels observed using magnifying NBI can serve as objective indicators for diagnosing SSLs with cancerous components with a high degree of accuracy.